The dental use for periodontal diseases under the national health insurance system in Taiwan in 2021 - Feng-Chou Cheng; Yin-Lin Wang; Chun-Pin Chiang (Elsevier, 2023)
Background/purpose: Periodontal disease is one of the main oral diseases in humans. This study investigated the dental use for periodontal diseases under the National Health Insurance system (NHI) system in Taiwan in 2021. Materials and methods: The population data and medical records of the NHI system were obtained from the websites of the Ministry of the Interior and the NHI Administration, respectively. The dental patient data were divided into 18 age groups to analyze the dental use indicators for periodontal diseases under the NHI system in Taiwan in 2021. Results: The dental use rate for treatment of periodontal diseases (including gingivitis and periodontitis) had the highest peak (51.85%) in the 5-9-year age group under the NHI system in Taiwan in 2021. It dropped abruptly to a lower point (38.20%) in the 15-19-year age group, fluctuated and declined gradually with increasing age, and finally dropped to the lowest point of 18.78% in the greater than 85-year age group. Furthermore, the number of out-patient visits per 1000 people showed a similar trend. However, the medical expenses per person also showed a similar trend except the findings of the highest peak in the 55-59-year age groups. Conclusion: Periodontal disease is still the main disease of the oral cavity in Taiwan. From a cost-effectiveness viewpoint, Taiwan government shall develop a better oral health policy to decrease the incidence of periodontal diseases and to prevent periodontal diseases from deteriorating into the end age of tooth loss for all citizens, especially for patients of special needs.